Retrospective distribution of Trypanosoma cruzi I genotypes in Colombia (2015)
Trypanosoma cruzi is the aetiological agent of Chagas disease, which affects approximately eight million people in the Americas. This parasite exhibits genetic variability, with at least six discrete typing units broadly distributed in the American continent. T. cruzi I (TcI) shows remarkable genetic diversity; a genotype linked to human infections and a domestic cycle of transmission have recently been identified, hence, this strain was named TcIDom. The aim of this work was to describe the spatiotemporal distribution of TcI subpopulations across humans, insect vectors and mammalian reservoirs in Colombia by means of molecular typing targeting the spliced leader intergenic region of mini-exon gene. We analysed 101 TcI isolates and observed a distribution of sylvatic TcI in 70% and TcIDom in 30%. In humans, the ratio was sylvatic TcI in 60% and TcIDom in 40%. In mammal reservoirs, the distribution corresponded to sylvatic TcI in 96% and TcIDom in 4%. Among insect vectors, sylvatic TcI was observed in 48% and TcIDom in 52%. In conclusion, the circulation of TcIDom is emerging in Colombia and this genotype is still adapting to the domestic cycle of transmission. The epidemiological and clinical implications of these findings are discussed herein. © 2015, Fundacao Oswaldo Cruz. All rights reserved.